Oxygen Variability and Tropical Atlantic Circulation Cruise No. M130 August 28 – October 3, 2016 Mindelo (Cape Verde) – Recife (Brazil) - Dengler, Marcus (GEOMAR, 2017)
A physical - biogeochemical survey was carried out in the northeastern tropical Atlantic and in the western tropical South Atlantic. The main objective of the works in the oxygen minimum zone of the eastern tropical North Atlantic was to improve oxygen budget estimates. Additional objectives were to investigate the role of zooplankton for fluxes of particulate and dissolved organic matter and to advance quantitative understanding of nitrogen fixation in the tropical Atlantic. The main objective of the measurements program in the western tropical South Atlantic was to investigate the variability of transport and water mass properties of the western boundary circulation. A major component of the work program was the recovery of nine and the redeployment of eight moorings. The moorings positioned off Cape Verde, in the tropical northeastern Atlantic and at the western boundary off Brazil are collecting velocity, oxygen, temperature, and salinity time series since several years. All moorings were successfully recovered and redeployed. Section work focused on 23°W from 15°N to 5.5°S, on 11.5°S from 32°W to the coast of Brazil and on 5°S from 29.5°W to the coast of Brazil. Parameters measured along the sections included temperature-salinity-depth, oxygen and turbulence profiles, lowered acoustic Doppler current profiles, underwater vision profiles, shipboard velocity profiles, multinet and Working Party 2 net casts, and photosynthetically active radiation profiles. Water samples were analyzed for numerous variables including salinity, oxygen concentrations, tracer concentrations (CFC-12, SF6, CF3SF5), nutrients in micro and nano range, and halocarbons. Filtered samples were taken for NanoSIMS, flow cytometry, dissolved organic phosphorus, DNA/RNA, particulate organic matter, particulate organic nitrogen, and chlorophyll a. Samples of Heme content and dissolved iron were taken from a towed trace metal clean fish. Furthermore, on-board incubations to quantify nitrogen and carbon fixation and primary productivity were ...